2011
DOI: 10.1007/s11665-010-9817-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sn and Zr on the Microstructure and Mechanical Properties of Ti-Ta-Based Shape Memory Alloys

Abstract: Ti-Ta binary shape memory alloys have attracted much interest due to the absence of toxic element and the low YoungÕs modulus. However, the effects of the third element on the microstructure and mechanical property had not been well understood. In the present study, the effect of Sn and Zr additions on the microstructure and mechanical property of Ti-35Ta (at.%) alloys has been investigated. The results show that the microstructure of the solution treated Ti-Ta-based alloys compose of equiaxial grains. The all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 19 publications
(12 reference statements)
1
15
0
Order By: Relevance
“…The well-known embrittling effects of the w phase and the probable difficulty of dislocation motion through the w phase may qualitatively account for the macroscopic brittle characteristics of the 1Mo alloy. A comparison of mechanical properties between the 5Mo alloy in present work and other recently reported b-titanium alloys [18,[44][45][46][47] has been displayed, Figure 7. The ascast 5Mo alloy shows superior tensile strength and comparable elongation.…”
Section: Resultsmentioning
confidence: 77%
“…The well-known embrittling effects of the w phase and the probable difficulty of dislocation motion through the w phase may qualitatively account for the macroscopic brittle characteristics of the 1Mo alloy. A comparison of mechanical properties between the 5Mo alloy in present work and other recently reported b-titanium alloys [18,[44][45][46][47] has been displayed, Figure 7. The ascast 5Mo alloy shows superior tensile strength and comparable elongation.…”
Section: Resultsmentioning
confidence: 77%
“…Also, small holes were observed at the grain boundaries, the location and nature of the cavities suggest that those were formed during the etching process for metallurgical structure observation, and would not influence the corrosion stability [ 40 ]. However, there is the possibility that the loss of titanium was also connected with the etching process, because the solution used for etching could be more favorable for boundaries of grains and titanium [ 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the elastic modulus of Ti25Ta25Nb3Sn (65 GPa) was lower than Ti CP (110 GPa) and Ti6Al4V. The Young's modulus value was slightly higher than Ti25Ta25Nb alloy (55 GPa), however, the addition of Sn suppresses the transformation β to α″ verified to ternary alloy in the elastic deformation known as 'double yielding' [23]. A drop was observed in Ti25Ta25Nb3Sn, which can be attributed to stressinduced α″ formation during deformation [24].…”
Section: Resultsmentioning
confidence: 99%